ISSUES OF IMPROVING THE EFFICIENCY OF INNOVATIVE PROJECTS OF INDUSTRIAL ENTERPRISES - Tuxtasinova Muhayyo Mirzasultonovna (European Science Publishing, 2024)
Nowadays all country such as in Uzbekistan paying attention the introduction of effective methods of financing innovative projects in accordance with national and international templates is an extremely important task. The experience of leading innovative enterprises shows that in the context of a shortage of resources, the application and improvement of modern modeling methods of large innovative projects is considered a vital necessity, which creates high efficiency in production.
Keywords: Innovation Strategy, Innovation Management, enterprise, financing, investment, Innovation, competition, startup.